Wybrane aspekty pracy dydaktyczno-wychowawczej realizowanej w szkolnych zespołach muzycznych = Selected aspects of teaching and conducting school music groups - Kumik, Ewa (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The text presents selected aspects of the teaching and educational work of the school music groups, as well as presents the benefits of a common music-making. It characterizes different types of music ensembles and specifies the tasks of the persons conducting music-making process. The author refers to the literature and to her own experiences resulting from conducting all sorts of vocal ensembles and choirs.
Keywords: zespół muzyczny; dydaktyka; wychowanie; ensembles; teaching; education; music-making